Activity-regulated cytoskeletal-associated protein (Arc) in presynaptic terminals and extracellular vesicles in hippocampal synapses - Ringsevjen, Håvard; Egbenya, Daniel Lawer; Bieler, Malte; Davanger, Svend; Hussain, Suleman (Frontiers in Molecular Neuroscience, 2023)
The activity-regulated cytoskeleton-associated protein (Arc/Arg3.1) is a neuron-specific immediate early gene (IEG) product. The protein regulates synaptic strength through modulation of spine density and morphology, AMPA receptor endocytosis, and as being part of a retrovirus-like inter-cellular communication mechanism. However, little is known about the detailed subsynaptic localization of the protein, and especially its possible presynaptic localization. In the present study, we provide novel electron microscopical data of Arc localization at hippocampal Schaffer collateral synapses in the CA1 region. The protein was found in both pre-and postsynaptic cytoplasm in a majority of synapses, associated with small vesicles. We also observed multivesicular body-like structures positive for Arc. Furthermore, the protein was located over the presynaptic active zone and the postsynaptic density. The relative concentration of Arc was 25% higher in the postsynaptic spine than in the presynaptic terminal. Notably, small extracellular vesicles labeled for Arc were detected in the synaptic cleft or close to the synapse, supporting a possible transsynaptic transmission of the protein in the brain.